Brachial Plexus With Two Trunks and Double Axillary Veins: Applied Importance and Clinical Implications - Prabhu, Latha V.; Kumar, Jwalaram; Sıngh, Gajendra (Fırat University, 2006)
During routine dissection in the Department of Anatomy following important anatomical variations on right side of a 30 years old male cadaver were observed. Brachial plexus comprised of only two trunks, the upper one was formed by union of C5, C6, C7 roots while the lower trunk was formed by union of C8, T1 roots.C5 root of brachial plexus was receiving a communicating branch from phrenic nerve. Double axillary veins were observed in the axillary region. Lesion or injury to upper trunk of brachial plexus in aforesaid case will manifest as wider spectrum of clinical signs with diffuse loss of function entirely different from the classic Erb–Duchenne palsy. This background of anatomical variations can help to minimize damage to important structures in the axilla during axillary dissection.©2006, Fırat Üniversitesi, Tıp Fakültesi

Anatomi anabilim dalında, 30 yaşındaki erkek bir kadavrada rutin diseksiyon sırasında sağ tarafta önemli anatomik varyasyonların varlığı gözlendi. Brachial plexus sadece iki trunkustan meydana gelmişti; üst trunkus C5, C6 ve C7 köklerinin birleşmesinden, alt trunkus ise C8 ve T1 köklerinin birleşmesinden oluşmuştu. Brachial plexus'un C5 kökü phrenic sinirden bir bağlantı dalı alıyordu. Aksiller bölgede çift aksiller ven olduğu gözlendi. Bu tip bir olguda, Brachial plexus'un yukarı kolunun lezyon veya yaralanması klasik Erb–Duchenne palsy'den tamamen farklı olarak tam fonksiyon kaybı ve daha yaygın klinik bulgularla karakterize bir tabloyla ortaya çıkacaktır. Bu gibi anatomik varyasyonların bilinmesi aksiller bölgede diseksiyon sırasında önemli yapıların hasarlanma riskinin en aza indirilmesine yardımcı olacaktır. ©2006, Fırat Üniversitesi, Tıp Fakültesi
İki Trunkuslu Pleksus Brachialis ve Çift Aksiller Ven: Uygulamada Önemi ve Klinik Anlamı